Energy and vulnerability: Exploring the energy poverty-risky sexual behavior nexus among young women in Ghana - Michael Adu Okyere; Aaron Kobina Christian; Felix Essel-Gaisey; Fawzia Muhammed Zuka (Elsevier, 2024)
While recent policy agendas have extensively addressed both energy poverty and risky sexual behavior separately, little research has explored their intersection. This pioneering study investigates the relationship between energy deprivation and risky sexual behavior in female youth. Utilizing data from the Demographic and Health Survey in Ghana and employing robust methodologies, including the Lewbel two-stage regression and alternative energy deprivation thresholds, our findings reveal an 8.2-8.7% increase in the likelihood of female youth engaging in risky sexual activities for each percentage increase in energy poverty. Notably, these estimates hold consistent across different wealth terciles and location subgroups. Furthermore, we identify the number of lifetime partners as a potential mediator through which energy poverty influences risky sexual behavior. In conclusion, our study emphasizes the urgent need for policymakers to prioritize the adoption of affordable energy services, particularly among impoverished and rural households. Such efforts have the potential to mitigate the adverse effects of energy poverty on risky sexual behavior. We also advocate for the integration of energy poverty eradication strategies within reproductive and sexual health programs to foster comprehensive development and well-being.